Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3389/fsurg.2022.997324
|View full text |Cite
|
Sign up to set email alerts
|

Specific steps in the operation determine resident speed: Experience with a live tissue simulation model of laparoscopic nephrectomy

Abstract: IntroductionIt is increasingly important to identify and eliminate inefficiencies in resident education. We hypothesize that slower performance of specific operative steps in laparoscopic nephrectomy accounts for much of the slower operative speed observed in junior residents vs. their senior colleagues. Therefore, we sought to evaluate the by-step time-differential between experienced senior residents and their junior colleagues in a live-tissue simulation.Materials and methodsResidents participated in our sw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…To overcome the potential drawbacks of assistants with low levels of experience during surgeries, training and simulation programs could indeed hold promise in enhancing outcomes [26][27][28][29]. It has been demonstrated that, considering the comparable clinical outcomes between patients treated by inexperienced surgeons and those treated by skilled surgeons, laparoscopic nephrectomy presents a viable opportunity for training purposes [5].…”
Section: Discussionmentioning
confidence: 99%
“…To overcome the potential drawbacks of assistants with low levels of experience during surgeries, training and simulation programs could indeed hold promise in enhancing outcomes [26][27][28][29]. It has been demonstrated that, considering the comparable clinical outcomes between patients treated by inexperienced surgeons and those treated by skilled surgeons, laparoscopic nephrectomy presents a viable opportunity for training purposes [5].…”
Section: Discussionmentioning
confidence: 99%